Efficient Preparation of Apically Substituted Diamondoid Derivatives - Kahl, Paul; Tkachenko, Boryslav A.; Novikovsky, Anatoliy A.; Becker, Jonathan; Dahl, Jeremy E. P.; Carlson, Robert M. K.; Fokin, Andrey A.; Schreiner, Peter R. (Synthesis, 2014)
We present an effective three-step chromatography-free sequence for the preparation of apical monohydroxy derivatives of diamantane, triamantane, and [121]tetramantane from the corresponding bis-apical diols utilizing tert-butyldimethylsilyl chloride as the monosilylating agent. The procedure was successfully applied to the monoprotection of several other aliphatic and aromatic diols. Additionally, 9-aminodiamantan-4-carboxylic acid, which has significant potential in medicinal and material sciences, was prepared through Ritter reaction of 4,9-dihydroxydiamantane in trifluoroacetic acid.
Keywords: amino acids; diols; monoprotection; nanostructures; silyl protecting groups